LITERATUR REVIEW: REVIEWING KADARZI BEHAVIOR TO REDUCE THE INCIDENCE OF STUNTING IN CHILDREN - Rizka Devi Widya Astuti; Isna Hudaya; Endang Surani (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2021)
Abstract Stunting is a chronic nutritional problem in children characterized by a shorter body size than children his age. Efforts to improve nutrition by the government to improve public health degrees through family-level health programs, one of which is through the nutrition-conscious family program (KADARZI). The method used is a literature review system contained in the database in the form of google scholar, sinta, and science direct as many as five articles that fit based on criteria with 2016-2021. Results from a literature review of five articles using a cross-sectional approach. The role of nutrition-conscious family behavior (KADARZI) to reduce the incidence of stunting in children is most effective if monitoring is carried out using anthropometric indicators (TB/U) and the application of nutrition-conscious family indicators (KADARZI). The better the application of nutrition-conscious family behavior (KADARZI) in the family, the better the nutritional status of toddlers, especially in providing optimal health protection through food consumed. keywords: Stunting, Behavior, Nutrition-Conscious Family